(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
The paper focuses on the derivation of the integral variants of Jensen’s inequality for convex functions of several variables. The work is based on the integral method, using convex combinations as input, and set barycentres as output.